2017
DOI: 10.1515/agp-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Isolated pliosaurid teeth from the Albian–Cenomanian (Cretaceous) of Annopol, Poland

Abstract: ABSTRACT:Madzia, D. and Machalski, M. 2017. Isolated pliosaurid teeth from the Albian-Cenomanian (Cretaceous) of Annopol, Poland. Acta Geologica Polonica, 67 (3), 393-403. Warszawa.Brachauchenine pliosaurids were a cosmopolitan clade of macropredatory plesiosaurs that are considered to represent the only pliosaurid lineage that survived the faunal turnover of marine amniotes during the JurassicCretaceous transition. However, the European record of the Early to early Late Cretaceous brachauchenines is largely l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…obs. ), and the assemblage of isolated tooth crowns once attributed to 'Polyptychodon' (Madzia, 2016;Madzia & Machalski, 2017), but differ from the teeth of Gallardosaurus iturraldei (Gasparini, 2009), Pliosaurus spp. (Knutsen, 2012;Benson et al 2013;Gasparini & O'Gorman, 2014;O'Gorman, Gasparini & Spolletti, 2018), Makhaira rossica (Fischer et al 2015), Stenorhynchosaurus munozi (Páramo-Fonseca et al 2016) and Luskhan itilensis (Fischer et al 2017), which are carinated and subtrihedral to trihedral, and the tooth crown of the Crimean pliosaurid (Zverkov, 2015), which is carinated and trihedral-to-'trapezoid' in its cross-sectional shape.…”
Section: E Comparisons To Dentitions Of Other Thalassophoneansmentioning
confidence: 89%
See 1 more Smart Citation
“…obs. ), and the assemblage of isolated tooth crowns once attributed to 'Polyptychodon' (Madzia, 2016;Madzia & Machalski, 2017), but differ from the teeth of Gallardosaurus iturraldei (Gasparini, 2009), Pliosaurus spp. (Knutsen, 2012;Benson et al 2013;Gasparini & O'Gorman, 2014;O'Gorman, Gasparini & Spolletti, 2018), Makhaira rossica (Fischer et al 2015), Stenorhynchosaurus munozi (Páramo-Fonseca et al 2016) and Luskhan itilensis (Fischer et al 2017), which are carinated and subtrihedral to trihedral, and the tooth crown of the Crimean pliosaurid (Zverkov, 2015), which is carinated and trihedral-to-'trapezoid' in its cross-sectional shape.…”
Section: E Comparisons To Dentitions Of Other Thalassophoneansmentioning
confidence: 89%
“…However, Madzia (2016) recently concluded that the dental material ascribed to P. interruptus does not show any autapomorphies and hypothesized that it is most likely too variable to represent a single species, prompting a revision of all other specimens attributed to this historical taxon (such studies are currently being undertaken; e.g. Sachs et al 2016b,c;Madzia & Machalski, 2017;Sachs et al 2018), rendering the taxon itself a nomen dubium. Indeed, detailed assessments of the dental morphology of pliosaurids with well-preserved dentitions might be crucial for these studies.…”
Section: Introductionmentioning
confidence: 99%
“…, ; Zverkov ; Madzia ; Páramo‐Fonseca et al . ; Madzia & Machalski ; Gómez‐Pérez & Noè (see Zverkov et al . , documents for detailed account of each taxon included).…”
Section: Methodsmentioning
confidence: 97%
“…Instead, if really belonging to a brachauchenine (and not a robust-toothed polycotylid), it seems to merely represent a relict of the once widespread pliosaurids. In turn, other isolated elements belonging to pliosaurids and polycotylids, such as those studied by Kear et al (2014), Madzia & Machalski (2017), , , Sachs et al (2020), and Zverkov & Pervushov (2020) might suggest a higher taxic diversity and a wider geographic distribution of the clades during the Albian-Turonian ('middle' Cretaceous).…”
Section: Sampling Biasmentioning
confidence: 98%